Methods for the synthesis of arsines and arsine dihalides - Yambushev, Farid Dgamaletdinovich (Revista de la Universidad del Zulia, 2019)
Arsenic is an essential biologically active element, and its compounds are used in various fields and areas of activity. Arsenic chemistry is widely used in agriculture, industry, and medicine. Many organic arsenic compounds have bactericidal and herbicidal properties necessary for practical use; some of them found its application in polymer chemistry. This necessitates the production of new substances with previously known properties. Therefore, the problem of studying methods for the synthesis of organic arsenic compounds is important and relevant.The present article is devoted to the analysis of methods for the synthesis of primary arsines and the corresponding arsine dihalides. Based on a study of literature containing a description of various methods for preparing compounds of this group, as well as on the basis of the results of own experimental studies, the author makes a choice in favor of the synthesis of primary aryl arsine dihalides by reduction of the corresponding arsonic acids. Subsequent substitution of halogen atoms can produce compounds of a specific structure. Thus, using aryl arsonic acids as starting products for the synthesis of subsequent classes of organic arsenic compounds, it is possible to obtain organic arsenic compounds of a given structure and complexity. A detailed description of the methods of conducting experiments is made, their comparative characteristics are given, and the physical properties of the obtained substances are described.